Sleep, Sleep Disturbances among Medical Students and their Academic Performance and Health: A Global Issue - Haque, Mainul; Kamal, Zubair (International Journal of Human and Health Sciences (IJHHS), 2019)
Sleep disorders, medical students, ICSD-3 classification, advanced sleep phase syndrome, excessive daytime sleepiness, burnout, sleep debt, nonrefreshing sleep, and academic performance. International Journal of Human and Health Sciences Vol. 03 No. 04 October’19 Page : 181-185